Foreign Accent and Toddlers' Word Learning: The Effect of Phonological Contrast. Issue 2 (3rd April 2018) - Newman, Rochelle S.; Morini, Giovanna; Kozlovsky, Penina; Panza, Sabrina
ABSTRACT: Prior work demonstrated that toddlers can learn words from a speaker with a foreign accent and generalize that learning to the native accent when the accented variation does not cross phoneme boundaries. The current study explores the situation in which a vowel in the foreign accent is produced such that it could be confused with a different intended vowel in the native accent. Children were taught two new word-object pairings by a foreign-accented speaker; when vowels were produced similarly across accents, toddlers aged 32 months successfully accommodated a change in accent between training and test; when a novel word contained a vowel that was more affected by accent, toddlers did not later recognize the words in their native accent. This suggests that toddlers may face added difficulty when learning words from speakers of different accents when there is the potential for phonetic confusion across vowels.